Material Flow Cost Accounting (MFCA) in the Canang Sari Production Value Chain: Material Optimization, Reduction of Religious Waste, and Empowerment of Female Craftsmen - Saputra, Komang Adi Kurniawan; Sancaya, I Wayan Werasmana (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study examines the application of Material Flow Cost Accounting (MFCA) in the canang sari production value chain in Bali to address material inefficiencies and the problem of religious waste, while simultaneously empowering female artisans. Through a qualitative case study approach with observations and in-depth interviews with artisan groups, the study revealed that approximately 30% of raw materials are wasted as production waste, considered a given cost. The MFCA analysis successfully identified hidden costs and critical inefficiencies, and revealed the dilemma between ritual sacredness and environmental responsibility in canang sari waste management. The research findings emphasize that MFCA implementation must be tailored to the unique socio-cultural and spiritual context. As an output, this study designed a simplified participatory MFCA model that serves as a tool to improve artisans’ financial literacy, optimize raw material use, and open a dialogue toward more ecological canang sari designs. Thus, this study not only extends the application of environmental accounting theory to the realm of the culture-based creative economy but also offers a holistic solution that synergizes economic efficiency, environmental sustainability, gender empowerment, and the preservation of local values.